Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1590/s1415-47572003000300015
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of the karyotype of the wasp Trypoxylon (Trypargilum) nitidum (Hymenoptera, Sphecidae) from the Rio Doce State Park, Minas Gerais, Brazil

Abstract: Cytogenetic analysis based on the distribution of C-bands showed two groups of karyotypes in a Trypoxylon nitidum population from the Rio Doce Park, State of Minas Gerais, Brazil. One of these groups, that was identical to a previously described karyotype (n = 15; 2n = 30), had a stable chromosome number and was rich in acrocentric chromosomes, whereas the other had a variable chromosome number (n = 12 to 14; 2n = 25 to 28) and was rich in pseudo-acrocentric chromosomes. We propose a hypothesis explaining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…However, most previous studies showed numeric variation as the main source of polymorphism (Brito et al, 1997;Araújo et al, 2002;Scher and Pompolo, 2003;Brown Jr. et al, 2004). The chromosome number 2n = 34 determined for Scaptotrigona xanthotricha agrees with previous studies on other Scaptotrigona species (Hoshiba and Imai, 1993;Rocha et al, 2003) and corroborates the numerical stability in the tribe Meliponini (Brito et al, 2003;Rocha et al, 2003;Costa et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, most previous studies showed numeric variation as the main source of polymorphism (Brito et al, 1997;Araújo et al, 2002;Scher and Pompolo, 2003;Brown Jr. et al, 2004). The chromosome number 2n = 34 determined for Scaptotrigona xanthotricha agrees with previous studies on other Scaptotrigona species (Hoshiba and Imai, 1993;Rocha et al, 2003) and corroborates the numerical stability in the tribe Meliponini (Brito et al, 2003;Rocha et al, 2003;Costa et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…In Hymenoptera, heterochromatin heteromorphism was observed in previous studies on the wasp Trypoxylon (Trypargilum) nitidum (Scher and Pompolo, 2003), and on the bees Partamona helleri (Brito et al, 1997) and Friesella schrottkyi (Mampumbu AR, unpublished results).…”
Section: Discussionmentioning
confidence: 52%
“…Specimens of Trypoxylon nitidum and Trypoxylon lactitarse showed a chromosome number within the range observed in this subgenus, whereas Trypoxylon rugifrons specimens showed the lowest chromosome number reported in the genus so far. The karyotypes and C-banding in Trypoxylon lactitarse and Trypoxylon nitidum from Camacanwere similar to those found by Gomes et al (1997) and Scher and Pompolo (2003) in the Brazilian Southeast region, revealing karyotype stability within these species along this range of the geographic distribution.…”
Section: Discussionsupporting
confidence: 86%
“…Araújo et al (2000) verified that the B chromosome in Trypoxylon albitarse was also stained by CMA3, similarly to the constitutive heterochromatin of all chromosomes in the complement, thus suggesting that the B chromosome originated from breaks in the constitutive heterochromatin and is maintained in the genome by centromeric “reactivation”. Scher and Pompolo (2003) did not report Trypoxylon nitidum specimens with 2n=29 in a population collected at the Parque Estadual do Rio Doce, in the state of Minas Gerais ( 19°30'S, 41°1'W ). This heterogeneity in karyotype over the distribution range highlights the need for further investigations in different localities to better resolve both karyotype distribution mapping and variation among Trypoxylon nitidum populations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation